(untitled) (Damascus University Journal of agriculture sciences, 2021)
This study was conducted in laboratories of agriculture college in Damascus university by collecting 14 randomized samples of mountain honeybees from three districted aria (Latakia, Homs and Damascus) during 2017 to determine physical properities ( total solid, refractive index, PH, electrical conductivity(EC), viscosity and color to know the quality of mountain honeybees in simple and fast way. Results showed that mountain honeybees In Damascus district had highest total solid(83.18%) with highest EC(0.54 m s cm-1 and lowest in moisture(14.29% by refractive index) , lowest viscosity(78 Piose) and lowest PH(4.12) comparing with Latakia and Homs districts. In addition , the color value by Hunter lab revealed that there were different color ranging from light yellow amber to heavy yellow amber and dark amber in all districts with the superiority for Damascus districts with red color for a* value . However, all the samples were accepted by Syrian standard (No.412 , 1987) with low value